A Cultural Approach to Peace Education - Templin, Carl; Sun, Jing (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
As we endeavor to develop as completely and comprehensively as possible the relatively new field of peace education it is important that we, as teachers, prepare ourselves to facilitate learning within and related to a diverse multiplicity of people. Central to our ability to be effective facilitators is a capacity to make intellectually attainable ideas that originate in cultural context with which students are unfamiliar. Equally important is the attainment of a propercommand of strategies that may be used to relate this and other information to the culture or cultures of which students are a part. Offering the opportunity for students to gain a broader cultural awareness and validating the cultural background from which students come has been one of the many foci of our work and our research at the Community center where we conducted the activities to be described. The result of this work and research can go a long way towards an answer to the question – why is culture an important facet of peace and peace education, and what role does it play? An answer to this question will provide future peace educators with a well-developed theoretical basis for their lessons, practical methods for teaching peace in a waythat students can understand, and a deeper appreciation for the approaches that many different cultures take to solve problems in just and equitable ways.